Perancangan UI/UX Aplikasi Audio Autonomous Sensoric Meridian Responses (ASMR) Untuk Penderita Insomnia Dengan Metode Design Thinking - Ami Wulandari; Yuli Maharetta Arianti; Nani Mintarsih; Atiqah Meutia Hilda (Prosiding Seminar Nasional Teknoka, 2024)
It is undeniable that technology is developing very rapidly, including in the field of information technology which has expanded to various sectors including the health sector. There is an openness of opportunities to handle problems by overcoming various problems through the use of mobile-based systems. One of them is by creating an application to overcome insomnia. This research aims to design the optimal Autonomous Sensoric Meridian Responses (ASMR) Audio UI / UX to overcome insomnia by applying the Design Thinking method, where there are 5 steps, namely, empathize, define, ideate, prototyping, and testing. Data collection is carried out using observation methods, interview psychologist discussion methods, and interview methods for 6 respondents to explore user problems. The results of usability testing using maze.co show a report value of 93 with 6 respondents, while through the questionnaire a value of 85 grade A, was obtained with 10 questions from the System Usability Scale (SUS). From the two testing methods, it was concluded that the Hoamz application prototype design has met user needs.